High-Precision Protein-Tracking With Interferometric Scattering Microscopy - Taylor, Richard W.; Holler, Cornelia; Mahmoodabadi, Reza Gholami; Küppers, Michelle; Dastjerdi, Houman Mirzaalian; Zaburdaev, Vasily; Schambony, Alexandra; Sandoghdar, Vahid (Frontiers in Cell and Developmental Biology, 2020)
The mobility of proteins and lipids within the cell, sculpted oftentimes by the organization of the membrane, reveals a great wealth of information on the function and interaction of these molecules as well as the membrane itself. Single particle tracking has proven to be a vital tool to study the mobility of individual molecules and unravel details of their behavior. Interferometric scattering (iSCAT) microscopy is an emerging technique well-suited for visualizing the diffusion of gold nanoparticle-labeled membrane proteins to a spatial and temporal resolution beyond the means of traditional fluorescent labels. We discuss the applicability of interferometric single particle tracking (iSPT) microscopy to investigate the minutia in the motion of a protein through measurements visualizing the mobility of the epidermal growth factor receptor in various biological scenarios on the live cell.